2016
DOI: 10.4102/sajhrm.v14i1.761
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personality types and leisure time activities amongst Casino employees’ workplace expectations

Abstract: Orientation: Associations between a person’s character strengths, happiness and well-being can be explained with the overlap that they have with personality. Casino employees’ working hours were and are increasing, which means that their leisure time is decreasing concomitantly, with only 20 hours per week being used in pursuit of leisure activities.Research purpose: The primary purpose of this research was to investigate 1502 casino employees’ personality types and the relationship it has on their leisure lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(90 reference statements)
2
8
0
Order By: Relevance
“…Our findings corroborated the outcome of Lu et al (2005) and Stephan et al (2014) who conclude in their investigations that personalities have a significant potential link between a person's personality and their quality of life in the workplace and their leisure time. These findings are also supported by the findings of Naude et al (2016) who reported that positive personality traits including cooperation and agreeability, as well as a fulfilling social life and contentment, were found to be positively correlated with sports leisure activities.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings corroborated the outcome of Lu et al (2005) and Stephan et al (2014) who conclude in their investigations that personalities have a significant potential link between a person's personality and their quality of life in the workplace and their leisure time. These findings are also supported by the findings of Naude et al (2016) who reported that positive personality traits including cooperation and agreeability, as well as a fulfilling social life and contentment, were found to be positively correlated with sports leisure activities.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings also suggest the implementation of recreational programs, potentially lessening illness-related absences (Parks & Steelman, 2008). A recent study has shown that casino employees partaking in leisurely activities were happier people, which translated into the workplace (Naude, Kruger, De Beer, Saayman, & Jonker, 2016). Such social activities provide avenues for employees to destress and engage with positive coping strategies, developing a balanced work-life culture.…”
Section: Managerial Implicationssupporting
confidence: 50%
“…That would be very difficult if it is work. Some authors took leisure as detachment from work (Beatty & Torbert, 2003;Isopahkala-Bouret, 2008;Mete, et al, 2012;Naude et al, 2016). While some authors took leisure as something that people do without fixed compensation (Mete et al, 2012), some would not consider compensation at all.…”
Section: Resultsmentioning
confidence: 99%
“…While some authors took leisure as something that people do without fixed compensation (Mete et al, 2012), some would not consider compensation at all. For those who did not consider leisure as being compensated, leisure was identified by intention and interest of people Serious participation in HRD intervention affects work performance (Wang & Wang, 2004) Self-reflection (Mete et al, 2012) Critical reflection plays an important role in problem solving and asking questions that affect individual and organization performance, and this could be related to individual and organizational learning (Van Woerkom, 2004) and support self-directed leadership (Nesbit, 2012) Sharing of experiences in serious leisure with others who might have different serious leisure activities (Beatty & Torbert, 2003) Learning from experience, directly or indirectly, affects the ability to improve at both the individual or organizational level (Smith, 2004) and organizational learning (Dixon, 1992) Intrinsic motivation of individual (Kashef & Nazri, 2015;Mete et al, 2012;Naude et al, 2016) The organization can succeed in the long term and sustain itself if it can attract employees that have high performance and engage with the organization. Those employees have intrinsic motivation from the work itself or the environment in the organization that is meaningful to them (Chalofsky & Krishna, 2009) Social motivation and support and surrounding factors (Kashef & Nazri, 2015;Naude et al, 2016;Petrou et al, 2017) HRD, human capital, emotional intelligence, the organization's products, and the internal and external environment affect each other (Brooks & Muyia Nafukho, 2006) and social support enhances performance (Bhanthumnavin, 2003) Changes in behavior and being active in serious leisure (Naude et al, 2016) Participation in HRD intervention such as training or coaching has a positive effect on performance, contribution in work, and job satisfaction (Rowold, 2008;Wang & Wang, 2004) Happiness and satisfaction in serious leisure activities (Kuykendall et al, 2018;Naude et al, 2016) HRD intervention that supports positive psychology and has a positive effect on work …”
Section: Resultsmentioning
confidence: 99%